The Impact of Corporate Governance (CG) on Firm Performance: Evidence from Emerging Countries Banking Industry - Bansal, Atul; Prasad Samontaray, Durga; Kumar, Rahul (Copernican Journal of Finance & Accounting, 2024)
The aim of the study to find if there is an impact caused by corporate governance CG on the firm performance (FP) using ROA as a measure. The study covered the listed 9 commercial banks in the Kuwait Stock Exchange. The period covered in this study is 10 years starting from 2011 until 2020. The study used the number of members of the board of directors (BoD), role duality of CEO and chairperson of the BoD and the number of women in the board of director as variables representing the CG. The data was processed and analyzed properly using regression model. The study concludes that there is significant relationship between (CG) and firm performance. Moreover, the variables of CG all have insignificant relationship with the ROA. Furthermore, the bank size which represent the total assets have significant positive relationship with the ROA. The researchers faced several limitations during the preparation of the study, a handful suggestions has been given for future researchers to overcome the limitation.